2009
DOI: 10.1097/tp.0b013e3181a44206
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Human Leukocyte Antigen and Donor-Specific Antibodies Detected by Luminex Posttransplant Serve as Biomarkers for Chronic Rejection of Renal Allografts

Abstract: We confirmed that HLAab produced even late after transplantation are detrimental to graft outcome. DSA were proven to have a strong adverse impact on graft survival. The results indicate that a posttransplant HLAab monitoring routine could be appropriate to improve long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
224
3
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(262 citation statements)
references
References 33 publications
26
224
3
9
Order By: Relevance
“…Recently published studies on pretransplant DSAs focused mainly on deceased donor transplants, as these are most prevalent in, for example, France, Germany, and the United States 17, 18, 19. Studies on living donor transplant are scarce; in a single‐center study, where 324 living donor transplants were analyzed, no significant difference in the 5‐year graft survival of patients with DSAs was found compared with patients with anti–blood type antibody, anti–HLA‐Abs, or no DSAs 20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently published studies on pretransplant DSAs focused mainly on deceased donor transplants, as these are most prevalent in, for example, France, Germany, and the United States 17, 18, 19. Studies on living donor transplant are scarce; in a single‐center study, where 324 living donor transplants were analyzed, no significant difference in the 5‐year graft survival of patients with DSAs was found compared with patients with anti–blood type antibody, anti–HLA‐Abs, or no DSAs 20.…”
Section: Discussionmentioning
confidence: 99%
“…For posttransplant DSAs determined using SAB assays, it was already shown that it has an adverse effect on graft survival 18. For our cohort, we can assess only the potential for confounding by de novo DSAs via the average number of HLA mismatches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both renal and cardiac transplantation there is evidence that development of HLA-specific antibodies, particularly if donorspecific, are associated with poor graft survival. [10][11][12] The development of BOS is the major cause of death beyond the first year after lung transplantation. 1,13 BOS is defined according to loss of lung function (forced expiratory volume in 1 second [FEV 1 ]) in proportion to maximal baseline value obtained post-transplantation in the absence of known acute causes of declining FEV 1 , such as acute rejection and infection.…”
mentioning
confidence: 99%
“…While DSA, either alone or in combination with microscopic evidence of microcirculation injury with or without C4d staining on kidney biopsy, are of most concern, the development of de novo nondonor HLA-specific (third party) antibodies are also, for reasons that are not clear, sometimes associated with an increased risk of graft loss (2,(4)(5)(6). One possible explanation for the association between de novo third party HLA-specific antibodies and inferior transplant outcome is that third party antibodies occur in conjunction with low level DSA or other non-HLAspecific antibodies that are not detected in the circulation because they have been absorbed by the kidney graft (2).…”
Section: Introductionmentioning
confidence: 99%